Revitalization Strategy of Laweut Dance Through Art Education in Indonesian Institute of Art and Culture, Aceh - Agustiina, Inna; Jazuli, Muhammad; Malarsih, Malarsih (Catharsis, 2019)
The existence of Laweut Dance is currently threatened to be extinct, even though Laweut Dance has many values ​​that are very beneficial for the community. This study examines the strategy of revitalizing Laweut Dance conducted by the Indonesian Institute of Art and Culture (ISBI). The method used in this study is qualitative. Data collection techniques are using observation, interview, and document study. The data validity technique uses triangulation and interactive data analysis technique. The results of this study are three strategies of Laweut Dance revitalization carried out by ISBI, namely, reconstruction, reformation, and refunctionalization. Reconstruction involves learning activities of Laweut Dance, which is made into Laweut Dance as learning material. Reformation included renewing the place, time, costumes and movements in the Laweut Dance performance, the renewal is carried out in accordance with the times and needs. Refunctionalization includes the renewal of the Laweut Dance function, which used to be Laweut Dance as an entertainment with the theme about the spirit of warfare, then a theme renewal, with the theme about the spirit of education. The implication of this study is that Laweut Dance can be used as a media and learning resource both formal and informal.